Analisis Epidemiologi Outbreak Campak Tahun 2025 di Puskesmas Sapta Taruna Pekanbaru - Ninna Apriani; Oktavia Dewi; Firdaus Riza (Published by Institut Teknologi Pendidikan Indonesia, 2026)
Measles remains a major public health concern, particularly in areas with inadequate immunization coverage. In 2025, a measles outbreak occurred in the working area of Sapta Taruna Primary Health Center, Pekanbaru. To describe the epidemiological characteristics of the outbreak by person, place, and time and to identify contributing risk factors. A descriptive outbreak investigation was conducted on 33 reported measles cases from January 2025 to February 2026. Data were collected from surveillance records, interviews, and field observations and analyzed descriptively. A total of 33 measles cases were identified with no deaths (CFR=0%). Most cases occurred among children aged 1–4 years (60.6%), and 69.7% had never received measles-rubella vaccination. Cases were concentrated in Tangkerang Labuai and Tangkerang Utara, showing a propagated outbreak pattern with a peak in October–November 2025. The outbreak was associated with low immunization coverage and increased exposure among susceptible populations. Strengthening routine immunization, early surveillance, and community education is essential to prevent future outbreaks.